Bidding factors in procurements of design documentation - Leśniak, Agnieszka (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The present study described a group of factors that may influence the decision to participate in a tender, when the subject of the order is the preparation of design documentation. The importance of the proposed factors was based on the opinions of designers who perform such services at the construction market. This analysis is followed by an assessment of the conformity of the opinions by means of the dispersion coefficient of relative ranking. The values of the dispersion coefficient of a relative classification differ considerably, from one another depending on the value under assessment. Yet, it is worth noticing that in the assessment of the factors influencing a bid/no bid decision, experts’ subjectivism cannot be avoided.